2016
DOI: 10.1186/s12888-016-0729-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-intensity narrow-band blue-light treatment compared to bright white-light treatment in sub-syndromal seasonal affective disorder

Abstract: BackgroundThe discovery of a novel photoreceptor in the retinal ganglion cells with a highest sensitivity of 470-490 nm blue light has led to research on the effects of short-wavelength light in humans. Several studies have explored the efficacy of monochromatic blue or blue-enriched light in the treatment of SAD. In this study, a comparison has been made between the effects of broad-wavelength light without ultraviolet (UV) wavelengths compared to narrow-band blue light in the treatment of sub-syndromal seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The therapeutic outcomes of exposure to blue light were found to be superior to those of red light;87,88 blue-enriched LED light was superior to placebo,40 but similar to blue light 89. In studies comparing the therapeutic outcomes after exposure to low-intensity narrow-band blue light with that of bright white light, no differences were found in the treatment effects in SAD90 or subsyndromal SAD (winter blues) 60. In a recent study comparing the therapeutic results after exposure to blue light (~465 nm) vs exposure to blue-free light (595–612 nm) no difference in treatment outcome was found 91.…”
Section: Light Treatmentmentioning
confidence: 91%
See 2 more Smart Citations
“…The therapeutic outcomes of exposure to blue light were found to be superior to those of red light;87,88 blue-enriched LED light was superior to placebo,40 but similar to blue light 89. In studies comparing the therapeutic outcomes after exposure to low-intensity narrow-band blue light with that of bright white light, no differences were found in the treatment effects in SAD90 or subsyndromal SAD (winter blues) 60. In a recent study comparing the therapeutic results after exposure to blue light (~465 nm) vs exposure to blue-free light (595–612 nm) no difference in treatment outcome was found 91.…”
Section: Light Treatmentmentioning
confidence: 91%
“…The existence of seasonal complaints, their severity, and a certain global seasonality score enable this instrument used in epidemiological studies to estimate SAD prevalence. Although the SPAQ is widely used, its validity has been criticized 5560. A number of new self-rating instruments have been developed for the assessment of seasonal depression, such as the Seasonal Health Questionnaire (SHQ)61 or more recently, the Seasonality Assessment Form 62.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Bright light therapy is the most common procedure in this category. It has been used especially for the treatment of seasonal affective disorder(Danilenko and Ivanova, 2015; Gordijn et al, 2012;Meesters et al, 2016Meesters et al, , 2011Oldham and Ciraulo, 2014;Pail et al, 2011;Prasko, 2008;Rastad et al, 2011) , but also in bipolar disorder (Pail et al, 2011;Prasko, 2008;Schwartz and Olds, 2015;Suzuki et al, 2016) and MDD (Al-Karawi and Jubair, 2016;Bais et al, 2016;Dridi et al, n.d.;Eniola et al, 2016;Oldham and Ciraulo, 2014;Pail et al, 2011;Schwartz and Olds, 2015), reportedly with a variable degree of therapeutic success. Light therapy as a nonpharmaceutical treatment has been recommended and is being tested as a method avoiding any pharmacological load during pregnancy and in perinatal depression (Bais et al, 2016;Crowley and Youngstedt, 2012).…”
Section: Insert Table 2 About Herementioning
confidence: 96%
“…Placebo-controlled trials of LED devices for patients with the disorder have shown efficacy for 398-lux narrow-band blue light (19), for 200-lux narrow-band blue light (20), and for 1,350-lux blueenriched white light (21). A trial comparing 98-lux narrowband blue light with 711-lux blue-enriched white light found similar therapeutic effect in patients with seasonal affective disorder (22), and a trial of 100-lux narrow-band blue light versus 10,000-lux bright white light found similar effect in patients with subsyndromal seasonal affective disorder (23). Given the absence of a placebo condition in the latter two studies, these findings should be considered preliminary.…”
Section: Led Beam Unitsmentioning
confidence: 98%